Fragile designs : a novel - Coble, Colleen; OverDrive, Inc. (Nashville, Tennessee : Thomas Nelson, 2024)
"Family secrets can be the most dangerous of all. The journey to find the truth and protect her family will have Carly delving deep into the lost treasures of Eastern Europe--if she can survive that long"--
Electronic audio file.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Family secrets -- Fiction; Novels; Electronic audio books; Thriller fiction